Exploring Moses’ Characterisation in Exodus 3:1–4:17 Using Conversational Analysis - Grier, Elizabeth (The Evangelical quarterly, 2025)
Conversational analysis is used to examine how Moses is presented in the dialogue of Exodus 3:1–4:17. Currently there exists extensive scholarship on the content of this call narrative of Moses, but very little which considers the linguistic structure of the conversation and how this is used to develop the characters and their relationship. Throughout the conversation, Moses is understandably fearful and reluctant, while Yahweh continually takes the initiative and seeks to reorient his thinking. Moses questions and even attempts to refuse God’s commands, in complete honesty before God. Conversational analysis highlights key features of the call narrative Gattung, where questions enable Yahweh to reorient Moses’ thinking, and where trust and obedience are required in response to Yahweh’s commission. Conversational analysis highlights the difference between Moses’ obedience and disobedience in his actions and words respectively. Significantly, conversational analysis reveals distinctions between the narrative’s presentation of Moses and his own self-presentation.